Anaesthesia in a Toxic Environment: Pressurised Intraperitoneal Aerosol Chemotherapy: A Retrospective Analysis - Rouche, Amir (Turk J Anaesthesiol Reanim, 2020)
OBJECTIVE: Pressurised intraperitoneal aerosol chemotherapy (PIPAC) is a new type of intraperitoneal chemotherapy for peritoneal carcinosis via minimally invasive surgery. This technique’s specificity is the remote application of the therapy because of the potential risk of exposure to toxic products. The present paper summarises the important aspects of PIPAC and analyses the anaesthetic outcomes. METHODS: This retrospective study included all patients undergoing PIPAC treatment between January 2015 and February 2018. Data on protocol adherence and perioperative anaesthetic complications and postoperative nausea and vomiting (PONV) and pain levels (visual analogue scale 0–10) from recovery room to 72 h were analysed. RESULTS: The overall analysis included 193 PIPAC procedures on 87 patients. Protocol adherence was high as regards the use of propofol (100%), rocuronium (98%), antiemetic prophylaxis (99%) and lidocaine intravenous (i.v.) (87%). No accidental exposure to chemotherapy occurred during the study period. Of the 87 patients, 6.3% suffered delayed recovery, 58% due to hypothermia and 42% due to excessive sedation or curarisation. In the recovery room, 16% of patients suffered moderate to severe pain, requiring >8 mg of morphine i.v., with average doses of 13.7 mg. Median postoperative pain scores were 1 and 3 at 12 h and 0 and 0 at 72 h at rest and mobilisation, respectively. PONV was observed in <10% of patients during the first 12 h, but in 40% at 72 h. CONCLUSION: A dedicated anaesthetic protocol and intraoperative safety checklist facilitates safe, well-tolerated anaesthesia for PIPAC treatments.